Hyperbranched polyethyleneimine, aqueous phase, composite nanofiltration membrane and preparation method thereof

By using the interfacial polymerization of hyperbranched polyethyleneimine and polyamide imide in the nanofiltration membrane, the composite nanofiltration membrane is formed, which solves the problem of instability and poor compatibility of the nanofiltration membrane, and improves the water flux and Anti-pollution ability, adapt to complex water quality treatment needs.

CN114797492BActive Publication Date: 2024-12-13OCHEMATE MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202110068306.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-01-19
Publication Date
2024-12-13
Estimated Expiration
2041-01-19

AI Technical Summary

Technical Problem

The selected layer structure of the existing nanofiltration membrane is unstable, and the base membrane and the separation layer material are poor, which leads to the easy separation layer and the base membrane being separated under extreme water quality conditions, affecting the long-term operation and pollution resistance of the nanofiltration membrane.

Method used

By reacting polyethyleneimine with glycidol in an organic solvent, hyperbranched polyethyleneimine is generated and interfacially polymerized with polyamideimide to form a composite nanofiltration membrane, increasing hydrophilic groups and improving The comprehensive performance and pollution resistance of the membrane.

Benefits of technology

The resulting composite nanofiltration membrane has higher water flux and desalination rate, while improving the anti-pollution ability, can be used for a longer period of time, and can adapt to different water quality treatment needs by regulating the amount of glycidol added.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002904923550000021
    Figure BDA0002904923550000021
  • Figure BDA0002904923550000031
    Figure BDA0002904923550000031
  • Figure BDA0002904923550000032
    Figure BDA0002904923550000032
Patent Text Reader

Abstract

The invention provides a hyperbranched polyethyleneimine composite nanofiltration membrane and a preparation method thereof. Polyethyleneimine is dissolved in an organic solvent to form an organic solution, and an alkali is added to the organic solution for reaction; then glycidol with a mass of 2-1000 times that of polyethyleneimine is added to continue the reaction, and hyperbranched polyethyleneimine is obtained after the reaction is continued. Modified polyethyleneimine is obtained by hyperbranched polymerization, which has a hyperbranched hydrophilic structure and can undergo interfacial polymerization with polyamide-imide to form a composite nanofiltration membrane with good comprehensive performance. The large number of hyperbranched hydrophilic structures possessed by the membrane make the membrane have better hydrophilicity on the one hand, and can have a better desalination rate while increasing its water flux; on the other hand, it also has better anti-pollution ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of water purification, and in particular to hyperbranched polyethyleneimine, an aqueous phase, a composite nanofiltration membrane and a preparation method thereof. Background Art

[0002] Membrane treatment technology plays an important role in the fields of seawater desalination, sewage treatment and special water separation. With the rapid development of my country in recent years, membrane treatment technology is facing the needs of more complex treatment objects, more diversified separation targets and energy-saving processes. Because nanofiltration membranes have selective separation functions under the coordinated control of pore size effect and charge effect, and the materials of nanofiltration membranes are highly designable, they can meet the needs of more complex and diversified fluid treatment; at the same time, nanofiltration membranes have higher flux at lower working pressures (0.2-1.0MPa), meeting the needs of energy-saving processes, so nanofiltration membranes have received widespread attention in many fields such as seawater desalination, recycling and special separation.

[0003] The current mainstream nanofiltration membrane is made by interfacial polymerization, in which a selective separation layer (mostly polyamide material) is compounded on the surface of a flat ultrafiltration membrane, and then the membrane is rolled into a membrane element. The membrane made by this method is called a rolled nanofiltration membrane. Compared with rolled membranes, hollow fiber membranes have a larger filling membrane area and significantly improved water production efficiency. In addition, the structure of the hollow fiber makes the membrane more resistant to pressure and impact, and has better anti-pollution ability. Therefore, hollow fiber nanofiltration membranes have great application potential in membrane treatment methods.

[0004] The raw material of common nanofiltration membranes is polyelectrolytes, and the driving force of the self-assembly process is the electrostatic force between positive and negative charges. Therefore, the selective layer structure of the nanofiltration membrane is often unstable; and the material compatibility between the base membrane and the separation layer is poor, and the two lack effective interaction at the interface, which makes the separation layer easy to separate from the base membrane during long-term operation of the nanofiltration membrane or under extreme water conditions. Therefore, further research and development of structurally stable nanofiltration membranes and improvement of the comprehensive performance of nanofiltration membranes are extremely important for the development and application of nanofiltration membranes. Summary of the invention

[0005] The first object of the present invention is to provide a hyperbranched polyethyleneimine, wherein polyethyleneimine is dissolved in an organic solvent to prepare an organic solution, and a base is added to the organic solution for reaction; then glycidol having a mass of 2-1000 times that of polyethyleneimine is added to continue the reaction to obtain a hyperbranched polyethyleneimine. The reaction equation is as follows:

[0006]

[0007] As an embodiment, the base is a strong base, including but not limited to one or both of potassium hydroxide and sodium hydroxide. A strong base is added to the organic solution of polyethyleneimine to react to obtain a polyethyleneimine macromolecular initiator, which then undergoes a ring-opening reaction with glycidol to obtain a hyperbranched polyethyleneimine monomer. The reaction time of the polyethyleneimine and the strong base is 1-20 hours, or the reaction time is 8-12 hours; the reaction temperature is 0-100°C, or the reaction temperature is 30-90°C, or the reaction temperature is 70-90°C.

[0008] As an embodiment, the mass fraction of polyethyleneimine in the organic solution is 0.01%-5.00%; or 0.50%-2.00%.

[0009] As an embodiment, the mass of the glycidol is 100-400 times the mass of polyethyleneimine.

[0010] As an embodiment, the temperature of the continued reaction is 80-200° C. The time of the continued reaction is 1-20 hours, or the time of the continued reaction is 8-12 hours.

[0011] As an implementation mode, after the reaction is continued, it is terminated with a terminator and filtered to obtain hyperbranched polyethyleneimine; the terminator is one or more of methanol, ethanol and petroleum ether.

[0012] As an embodiment, the organic solvent is one or more of amyl acetate, ethyl acetate, and cyclohexane.

[0013] The second object of the present invention is to provide a hyperbranched polyethyleneimine aqueous phase, wherein the hyperbranched polyethyleneimine is dissolved in pure water to obtain a hyperbranched polyethyleneimine aqueous phase with a mass fraction of 0.20%-2.0%.

[0014] The third object of the present invention is to provide a method for preparing a composite nanofiltration membrane, comprising the following steps: step 1, placing a base membrane into the above-mentioned hyperbranched polyethyleneimine aqueous solution for soaking once to obtain a base membrane with a hyperbranched polyethyleneimine aqueous phase attached to the surface; step 2, placing the base membrane with a hyperbranched polyethyleneimine aqueous phase attached to the surface in step 1 into a polyamide-imide oil phase for soaking for a second time, and reacting to obtain a composite nanofiltration membrane.

[0015] The reactants for the second soaking are as follows,

[0016]

[0017] The products of the second soaking are as follows:

[0018]

[0019] The present application obtains hyperbranched modified polyethyleneimine after being modified by glycidol, which has a large amount of hydrophilic groups and can form a composite nanofiltration membrane by interfacial polymerization with polyamide-imide, and the generated composite nanofiltration membrane has good comprehensive performance. Because the composite nanofiltration membrane has a large amount of hyperbranched hydrophilic structures (hydroxyls), it can have a good rejection rate while improving its water flux, and because these hydrophilic groups with hydrophilicity exist, it can also improve its anti-pollution ability. In addition, since the number of hyperbranched hydrophilic groups can be regulated by glycidol, it can be used for more diversified and more complicated water treatment. At the same time, the presence of polyhydroxyls between the basement membrane and the separation layer makes the coating and the basement membrane more firmly combined.

[0020] As an embodiment, the soaking time is 1-60 minutes; or the soaking time is 1-10 minutes.

[0021] As an implementation method, the substrate is soaked and cleaned with pure water before soaking once in step 1. The purpose of soaking with pure water first is to clean the base film and remove dust, etc.; the purpose of cleaning with pure water again is to wet the base film so that it can be better immersed in the water phase.

[0022] As an embodiment, the base membrane material in step one is one or more of polysulfone, polyethersulfone, polyacrylonitrile, polyimide, polyvinyl chloride, chlorinated polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyester fibers, polyvinyl alcohol fibers, polyetherimide, sulfonated polyetheretherketone, and cellulose acetate.

[0023] As an implementation mode, the second soaking in step 2 is followed by draining; the draining is performed by vertical hanging, such as vertical hanging for 1-60 minutes; or, vertical hanging for 2-30 minutes.

[0024] As an embodiment, the mass fraction of polyamide-imide in the organic solution in step 2 is 0.10%-1.0%; or the mass fraction is 0.20-0.50%.

[0025] As an embodiment, the secondary immersion time is 1-60 minutes; or, the secondary immersion time is 2-10 minutes.

[0026] As an embodiment, in the step 2, the composite nanofiltration membrane after the secondary immersion reaction is placed in a 60-100° C. or 60-80° C. forced air oven for drying, for example, for 1-10 minutes.

[0027] The fourth object of the present invention is to provide a composite nanofiltration membrane, which is prepared by the above-mentioned composite nanofiltration membrane preparation method. Because it has a large number of hyperbranched hydrophilic structures (hydroxyl groups), it has good comprehensive performance.

[0028] Beneficial effects of the present invention:

[0029] The present invention obtains a hyperbranched modified polyethyleneimine after modification with glycidol, which has a large number of hydrophilic groups and can undergo interfacial polymerization with polyamide-imide to form a composite nanofiltration membrane. The generated composite nanofiltration membrane has good comprehensive performance. The large number of hyperbranched hydrophilic structures of the composite nanofiltration membrane make the composite nanofiltration membrane have better hydrophilicity on the one hand, and can have a good desalination rate while improving its water flux; on the other hand, it has better anti-pollution ability, and with the pressureless flushing pipeline, it can wash away the pollution attached to the surface of the composite nanofiltration membrane, so that the composite nanofiltration membrane has a longer service life. In addition, by regulating the amount of glycidol added, composite nanofiltration membranes with different structures or different hyperbranching ratios can be obtained to improve the comprehensive performance of the composite nanofiltration membrane, for more complex and diversified treatment situations, such as highly polluted industrial wastewater, daily drinking water, etc. DETAILED DESCRIPTION

[0030] The present invention is described in detail in the following specific examples, but the present invention is not limited to the following examples.

[0031] Example 1

[0032] The polyethyleneimine is dissolved in amyl acetate to prepare a polyethyleneimine organic solution with a mass fraction of 2.00%, potassium hydroxide is added for reaction, and then 1000 times of glycidol is added slowly or all at once according to the metered amount, and the reaction is carried out at 200° C. for 20 hours. After termination with methanol, precipitation is carried out, and filtration is performed to obtain hyperbranched polyethyleneimine.

[0033] Example 2

[0034] The hyperbranched polyethyleneimine in Example 1 was dissolved in pure water to obtain a hyperbranched polyethyleneimine aqueous phase with a mass fraction of 0.50%.

[0035] Example 3

[0036] Dissolve polyethyleneimine in amyl acetate to prepare a polyethyleneimine organic solution with a mass fraction of 2.00%, add potassium hydroxide to react, add 50 times of glycidol slowly or all at once according to the metered amount, react at 80°C for 2 hours, terminate with methanol, precipitate, filter, and obtain hyperbranched polyethyleneimine. Finally, dissolve the hyperbranched polyethyleneimine in pure water to obtain a hyperbranched polyethyleneimine aqueous phase with a mass fraction of 0.50%.

[0037] Example 4

[0038] Dissolve polyethyleneimine in ethyl acetate to prepare a polyethyleneimine organic solution with a mass fraction of 2.00%, add potassium hydroxide to react, add 50 times of glycidol slowly or all at once according to the metered amount, react at 80°C for 2 hours, terminate with ethanol, precipitate, filter, and obtain hyperbranched polyethyleneimine. Finally, dissolve the hyperbranched polyethyleneimine in pure water to obtain a hyperbranched polyethyleneimine aqueous phase with a mass fraction of 0.30%.

[0039] Example 5

[0040] Dissolve polyethyleneimine in ethyl acetate to prepare a polyethyleneimine organic solution with a mass fraction of 2.00%, add potassium hydroxide for reaction, add 100 times of glycidol slowly or all at once according to the metered amount, react at 100°C for 4 hours, terminate with petroleum ether, precipitate, filter, and obtain hyperbranched polyethyleneimine. Finally, dissolve the hyperbranched polyethyleneimine in pure water to obtain a hyperbranched polyethyleneimine aqueous phase with a mass fraction of 0.20%.

[0041] Example 6

[0042] Polyethyleneimine is dissolved in cyclohexane to prepare a polyethyleneimine organic solution with a mass fraction of 2.00%, potassium hydroxide is added for reaction, 100 times of glycidol is added slowly or all at once according to the metered amount, the reaction is carried out at 100°C for 4 hours, and after being terminated with methanol, the solution is precipitated and filtered to obtain hyperbranched polyethyleneimine. Finally, the hyperbranched polyethyleneimine is dissolved in pure water to obtain a hyperbranched polyethyleneimine aqueous phase with a mass fraction of 0.90%.

[0043] Example 7

[0044] Dissolve polyethyleneimine in ethyl acetate to prepare a polyethyleneimine organic solution with a mass fraction of 2.00%, add potassium hydroxide to react, add 200 times of glycidol slowly or all at once according to the metered amount, react at 120°C for 6 hours, terminate with ethanol, precipitate, filter, and obtain hyperbranched polyethyleneimine. Finally, dissolve the hyperbranched polyethyleneimine in pure water to obtain a hyperbranched polyethyleneimine aqueous phase with a mass fraction of 0.40%.

[0045] Example 8

[0046] Dissolve polyethyleneimine in cyclohexane to prepare a polyethyleneimine organic solution with a mass fraction of 2.00%, add potassium hydroxide to react, add 200 times of glycidol slowly or all at once according to the metered amount, react at 120°C for 6 hours, terminate with methanol, precipitate, filter, and obtain hyperbranched polyethyleneimine. Finally, dissolve the hyperbranched polyethyleneimine in pure water to obtain a hyperbranched polyethyleneimine aqueous phase with a mass fraction of 0.30%.

[0047] Example 9

[0048] Dissolve polyethyleneimine in amyl acetate to prepare a polyethyleneimine organic solution with a mass fraction of 2.00%, add potassium hydroxide to react, add 400 times of glycidol slowly or all at once according to the metered amount, react at 140°C for 8 hours, terminate with methanol, precipitate, filter, and obtain hyperbranched polyethyleneimine. Finally, dissolve the hyperbranched polyethyleneimine in pure water to obtain a hyperbranched polyethyleneimine aqueous phase with a mass fraction of 0.60%.

[0049] Example 10

[0050] Dissolve polyethyleneimine in ethyl acetate to prepare a polyethyleneimine organic solution with a mass fraction of 2.00%, add potassium hydroxide to react, add 400 times of glycidol slowly or all at once according to the metered amount, react at 140°C for 8 hours, terminate with methanol, precipitate, filter, and obtain hyperbranched polyethyleneimine. Finally, dissolve the hyperbranched polyethyleneimine in pure water to obtain a hyperbranched polyethyleneimine aqueous phase with a mass fraction of 0.30%.

[0051] Embodiment 11

[0052] Dissolve polyethyleneimine in amyl acetate to prepare a polyethyleneimine organic solution with a mass fraction of 2.00%, add potassium hydroxide to react, add 800 times of glycidol slowly or all at once according to the metered amount, react at 180°C for 12 hours, terminate with petroleum ether, precipitate, filter, and obtain hyperbranched polyethyleneimine. Finally, dissolve the hyperbranched polyethyleneimine in pure water to obtain a hyperbranched polyethyleneimine aqueous phase with a mass fraction of 0.70%.

[0053] Example 12

[0054] Dissolve polyethyleneimine in cyclohexane to prepare a polyethyleneimine organic solution with a mass fraction of 2.00%, add potassium hydroxide to react, add 800 times of glycidol slowly or all at once according to the metered amount, react at 180°C for 12 hours, terminate with methanol, precipitate, filter, and obtain hyperbranched polyethyleneimine. Finally, dissolve the hyperbranched polyethyleneimine in pure water to obtain a hyperbranched polyethyleneimine aqueous phase with a mass fraction of 0.40%.

[0055] Example 13

[0056] After the base membrane made of polyimide material is immersed in the hyperbranched polyethyleneimine aqueous phase of Example 2 once, the base membrane with the hyperbranched polyethyleneimine aqueous phase attached to the surface is taken out; then the base membrane with the hyperbranched polyethyleneimine aqueous phase attached to the surface is immersed in a polyamide-imide organic solution with a mass fraction of 0.50% for a second time, wherein the organic solvent of the polyamide-imide organic solution is amyl acetate; after the second immersion, the base membrane that has been immersed for the second time is placed in a 60-100°C forced air oven and kept for 1-10 minutes to obtain a composite nanofiltration membrane.

[0057] Example 14 (Comparative Example)

[0058] A polysulfone hollow fiber ultrafiltration membrane is used as a base membrane. The base membrane is first soaked in pure water, then taken out and washed with pure water, and then the washed base membrane is placed in a polyethyleneimine aqueous solution (polyethyleneimine aqueous phase) with a mass fraction of 0.20% and kept for 2 minutes; then the base membrane is taken out from the polyethyleneimine aqueous solution, hung vertically for 10 minutes, and the base membrane is drained; then the base membrane adsorbed with the water phase is immersed in a polyamide-imide organic solution with a mass fraction of 0.10% and kept for 2 minutes, wherein the organic solvent is cyclohexane; the above base membrane is taken out from the polyamide-imide organic solution, placed in an 80°C forced air oven and kept for 8 minutes, and a polysulfone composite nanofiltration membrane is obtained after drying.

[0059] At 25℃±2℃ and 0.31MPa pressure, the separation performance of the composite nanofiltration membrane was tested with 250ppm magnesium sulfate solution as the test water sample. The results are as follows: the desalination rate of the composite nanofiltration membrane is 92.2%, and the water flux is 31.5L / m 2 h.

[0060] In order to evaluate the anti-pollution ability of the composite nanofiltration membrane, industrial wastewater (organic wastewater, COD (chemical oxygen demand) greater than 600ppm, sulfate greater than 600ppm, amine nitrogen greater than 45ppm) was taken as the water sample at a pressure of 0.31MPa, and the composite nanofiltration membrane was run for 1h, and then the composite nanofiltration membrane was rinsed with pure water for 2 minutes; then at a pressure of 0.31MPa, 250ppm magnesium sulfate solution was used as the test water sample, and the separation performance of the composite nanofiltration membrane was retested. The results are as follows: the desalination rate of the composite nanofiltration membrane is 82.3%, and the water flux is 22.5L / m 2 h.

[0061] Embodiment 15

[0062] A polysulfone hollow fiber ultrafiltration membrane is used as a base membrane. The base membrane is first soaked in pure water, then taken out and washed with pure water, and then the washed base membrane is placed in the hyperbranched polyethyleneimine aqueous phase described in Example 3 and kept for 2 minutes; then the base membrane is taken out from the hyperbranched polyethyleneimine aqueous phase, hung vertically for 10 minutes, and the base membrane is drained; then the base membrane adsorbed with the hyperbranched polyethyleneimine aqueous phase is immersed in a polyamide-imide organic solution with a mass fraction of 0.30% and kept for 2 minutes, wherein the organic solvent is amyl acetate; the above-mentioned base membrane is taken out from the polyamide-imide organic solution (oil phase), placed in an 80°C forced air oven and kept for 8 minutes, and a polysulfone composite nanofiltration membrane is obtained after drying.

[0063] At 25℃±2℃ and 0.31MPa pressure, the separation performance of the composite nanofiltration membrane was tested with 250ppm magnesium sulfate solution as the test water sample. The results are as follows: the desalination rate of the composite nanofiltration membrane is 93.6%, and the water flux is 32.1L / m2 h.

[0064] In order to evaluate the anti-pollution ability of the composite nanofiltration membrane, industrial wastewater (organic wastewater, COD (chemical oxygen demand) greater than 600ppm, sulfate greater than 600ppm, amine nitrogen greater than 45ppm) was taken as the water sample at a pressure of 0.31MPa, and the composite nanofiltration membrane was run for 1h, and then the composite nanofiltration membrane was rinsed with pure water for 2 minutes; then at a pressure of 0.31MPa, 250ppm magnesium sulfate solution was used as the test water sample, and the separation performance of the composite nanofiltration membrane was retested. The results are as follows: the desalination rate of the composite nanofiltration membrane is 88.7%, and the water flux is 25.2L / m 2 h.

[0065] Example 16

[0066] A polysulfone hollow fiber ultrafiltration membrane is used as a base membrane. The base membrane is first soaked in pure water, then taken out and washed with pure water, and then the washed base membrane is placed in the hyperbranched polyethyleneimine aqueous phase described in Example 4 and kept for 2 minutes; then the base membrane is taken out from the hyperbranched polyethyleneimine aqueous phase, hung vertically for 10 minutes, and the base membrane is drained; then the base membrane adsorbed with the aqueous phase is immersed in a polyamide-imide organic solution with a mass fraction of 0.50% and kept for 2 minutes, wherein the organic solvent is ethyl acetate; the above base membrane is taken out from the polyamide-imide organic solution, placed in an 80°C forced air oven and kept for 8 minutes, and a polysulfone composite nanofiltration membrane is obtained after drying.

[0067] At 25℃±2℃ and 0.31MPa pressure, the separation performance of the composite nanofiltration membrane was tested with 250ppm magnesium sulfate solution as the test water sample. The results are as follows: the desalination rate of the composite nanofiltration membrane is 92.5%, and the water flux is 32.75L / m 2 h.

[0068] In order to evaluate the anti-pollution ability of the composite nanofiltration membrane, industrial wastewater (organic wastewater, COD (chemical oxygen demand) greater than 600ppm, sulfate greater than 600ppm, amine nitrogen greater than 45ppm) was taken as the water sample at a pressure of 0.31MPa, and the composite nanofiltration membrane was run for 1h, and then the composite nanofiltration membrane was rinsed with pure water for 2 minutes; then at a pressure of 0.31MPa, 250ppm magnesium sulfate solution was used as the test water sample, and the separation performance of the composite nanofiltration membrane was retested. The results are as follows: the desalination rate of the composite nanofiltration membrane is 89.2%, and the water flux is 26.8L / m 2 h.

[0069] Embodiment 17

[0070] A polysulfone hollow fiber ultrafiltration membrane is used as a base membrane. The base membrane is first soaked in pure water, then taken out and washed with pure water, and then the washed base membrane is placed in the hyperbranched polyethyleneimine aqueous phase described in Example 5 and kept for 2 minutes; then the base membrane is taken out from the hyperbranched polyethyleneimine aqueous phase, hung vertically for 10 minutes, and the base membrane is drained; then the base membrane adsorbed with the aqueous phase is immersed in a polyamide-imide organic solution with a mass fraction of 0.20% and kept for 2 minutes, wherein the organic solvent is ethyl acetate; the above base membrane is taken out from the polyamide-imide organic solution, placed in an 80°C forced air oven and kept for 8 minutes, and a polysulfone composite nanofiltration membrane is obtained after drying.

[0071] At 25℃±2℃ and 0.31MPa pressure, the separation performance of the composite nanofiltration membrane was tested with 250ppm magnesium sulfate solution as the test water sample. The results are as follows: the desalination rate of the composite nanofiltration membrane is 96.3%, and the water flux is 34.2L / m 2 h.

[0072] In order to evaluate the anti-pollution ability of the composite nanofiltration membrane, industrial wastewater (organic wastewater, COD (chemical oxygen demand) greater than 600ppm, sulfate greater than 600ppm, amine nitrogen greater than 45ppm) was taken as the water sample at a pressure of 0.31MPa, and the composite nanofiltration membrane was run for 1h, and then the composite nanofiltration membrane was rinsed with pure water for 2 minutes; then at a pressure of 0.31MPa, 250ppm magnesium sulfate solution was used as the test water sample, and the separation performance of the composite nanofiltration membrane was retested. The results are as follows: the desalination rate of the composite nanofiltration membrane is 93.2%, and the water flux is 28.3L / m 2 h.

[0073] Embodiment 18

[0074] A polysulfone hollow fiber ultrafiltration membrane is used as a base membrane. The base membrane is first soaked in pure water, then taken out and washed with pure water, and then the washed base membrane is placed in the hyperbranched polyethyleneimine aqueous phase described in Example 6 and kept for 2 minutes; then the base membrane is taken out from the hyperbranched polyethyleneimine aqueous phase, hung vertically for 10 minutes, and the base membrane is drained; then the base membrane adsorbed with the aqueous phase is immersed in a polyamide-imide organic solution with a mass fraction of 0.10% and kept for 2 minutes, wherein the organic solvent is cyclohexane; the above base membrane is taken out from the polyamide-imide organic solution, placed in an 80°C forced air oven and kept for 8 minutes, and a polysulfone composite nanofiltration membrane is obtained after drying.

[0075] At 25℃±2℃ and 0.31MPa pressure, the separation performance of the composite nanofiltration membrane was tested with 250ppm magnesium sulfate solution as the test water sample. The results are as follows: the desalination rate of the composite nanofiltration membrane is 96.5%, and the water flux is 34.7L / m 2 h.

[0076] In order to evaluate the anti-pollution ability of the composite nanofiltration membrane, industrial wastewater (organic wastewater, COD (chemical oxygen demand) greater than 600ppm, sulfate greater than 600ppm, amine nitrogen greater than 45ppm) was taken as the water sample at a pressure of 0.31MPa, and the composite nanofiltration membrane was run for 1h, and then the composite nanofiltration membrane was rinsed with pure water for 2 minutes; then at a pressure of 0.31MPa, 250ppm magnesium sulfate solution was used as the test water sample, and the separation performance of the composite nanofiltration membrane was retested. The results are as follows: the desalination rate of the composite nanofiltration membrane is 93.5%, and the water flux is 28.4L / m 2 h.

[0077] Embodiment 19

[0078] A polysulfone hollow fiber ultrafiltration membrane is used as a base membrane. The base membrane is first soaked in pure water, then taken out and washed with pure water, and then the washed base membrane is placed in the hyperbranched polyethyleneimine aqueous phase described in Example 7 and kept for 2 minutes; then the base membrane is taken out from the hyperbranched polyethyleneimine aqueous phase, hung vertically for 10 minutes, and the base membrane is drained; then the base membrane adsorbed with the aqueous phase is immersed in a polyamide-imide organic solution with a mass fraction of 0.40% and kept for 2 minutes, wherein the organic solvent is ethyl acetate; the above-mentioned base membrane is taken out from the polyamide-imide organic solution, placed in an 80°C forced air oven and kept for 8 minutes, and a polysulfone composite nanofiltration membrane is obtained after drying.

[0079] At 25℃±2℃ and 0.31MPa pressure, the separation performance of the composite nanofiltration membrane was tested with 250ppm magnesium sulfate solution as the test water sample. The results are as follows: the desalination rate of the composite nanofiltration membrane is 94.4%, and the water flux is 36.8L / m 2 h.

[0080] In order to evaluate the anti-pollution ability of the composite nanofiltration membrane, industrial wastewater (organic wastewater, COD (chemical oxygen demand) greater than 600ppm, sulfate greater than 600ppm, amine nitrogen greater than 45ppm) was taken as the water sample at a pressure of 0.31MPa, and the operation was carried out for 1h, and then the composite nanofiltration membrane was rinsed with pure water for 2 minutes; then at a pressure of 0.31MPa, 250ppm magnesium sulfate solution was used as the test water sample, and the separation performance of the composite nanofiltration membrane was retested. The results are as follows: the desalination rate of the composite nanofiltration membrane is 92.3%, and the water flux is 30.6L / m 2 h.

[0081] Embodiment 20

[0082] A polysulfone hollow fiber ultrafiltration membrane is used as a base membrane. The base membrane is first soaked in pure water, then taken out and washed with pure water, and then the washed base membrane is placed in the hyperbranched polyethyleneimine aqueous phase described in Example 8 and kept for 2 minutes; then the base membrane is taken out from the hyperbranched polyethyleneimine aqueous phase, hung vertically for 10 minutes, and the base membrane is drained; then the base membrane adsorbed with the aqueous phase is immersed in a polyamide-imide organic solution with a mass fraction of 0.20% and kept for 2 minutes, wherein the organic solvent is cyclohexane; the above base membrane is taken out from the polyamide-imide organic solution, placed in an 80°C forced air oven and kept for 8 minutes, and a polysulfone composite nanofiltration membrane is obtained after drying.

[0083] At 25℃±2℃ and 0.31MPa pressure, the separation performance of the composite nanofiltration membrane was tested with 250ppm magnesium sulfate solution as the test water sample. The results are as follows: the desalination rate of the composite nanofiltration membrane is 94.6%, and the water flux is 37.1L / m 2 h.

[0084] In order to evaluate the anti-pollution ability of the composite nanofiltration membrane, industrial wastewater (organic wastewater, COD (chemical oxygen demand) greater than 600ppm, sulfate greater than 600ppm, amine nitrogen greater than 45ppm) was taken as the water sample at a pressure of 0.31MPa, and the operation was carried out for 1h, and then the composite nanofiltration membrane was rinsed with pure water for 2 minutes; then at a pressure of 0.31MPa, 250ppm magnesium sulfate solution was used as the test water sample, and the separation performance of the composite nanofiltration membrane was retested. The results are as follows: the desalination rate of the composite nanofiltration membrane is 91.9%, and the water flux is 31.5L / m 2 h.

[0085] Embodiment 21

[0086] A polysulfone hollow fiber ultrafiltration membrane is used as a base membrane. The base membrane is first soaked in pure water, then taken out and washed with pure water, and then the washed base membrane is placed in the hyperbranched polyethyleneimine aqueous phase described in Example 9 and kept for 2 minutes; then the base membrane is taken out from the hyperbranched polyethyleneimine aqueous phase, hung vertically for 10 minutes, and the base membrane is drained; then the base membrane adsorbed with the aqueous phase is immersed in a polyamide-imide organic solution with a mass fraction of 0.40% and kept for 2 minutes, wherein the organic solvent is amyl acetate; the above base membrane is taken out from the polyamide-imide organic solution, placed in an 80°C forced air oven and kept for 8 minutes, and a polysulfone composite nanofiltration membrane is obtained after drying.

[0087] At 25℃±2℃ and 0.31MPa pressure, the separation performance of the composite nanofiltration membrane was tested with 250ppm magnesium sulfate solution as the test water sample. The results are as follows: the desalination rate of the composite nanofiltration membrane is 92.3%, and the water flux is 40.1L / m 2 h.

[0088] In order to evaluate the anti-pollution ability of the composite nanofiltration membrane, industrial wastewater (organic wastewater, COD (chemical oxygen demand) greater than 600ppm, sulfate greater than 600ppm, amine nitrogen greater than 45ppm) was taken as the water sample at a pressure of 0.31MPa, and the composite nanofiltration membrane was run for 1h, and then the composite nanofiltration membrane was rinsed with pure water for 2 minutes; then at a pressure of 0.31MPa, 250ppm magnesium sulfate solution was used as the test water sample, and the separation performance of the composite nanofiltration membrane was retested. The results are as follows: the desalination rate of the composite nanofiltration membrane is 91.5%, and the water flux is 33.5L / m 2 h.

[0089] Embodiment 22

[0090] A polysulfone hollow fiber ultrafiltration membrane is used as a base membrane. The base membrane is first soaked in pure water, then taken out and washed with pure water, and then the washed base membrane is placed in the hyperbranched polyethyleneimine aqueous phase described in Example 10 and kept for 2 minutes; then the base membrane is taken out from the hyperbranched polyethyleneimine aqueous phase, hung vertically for 10 minutes, and the base membrane is drained; then the base membrane adsorbed with the aqueous phase is immersed in a polyamide-imide organic solution with a mass fraction of 0.30% and kept for 2 minutes, wherein the organic solvent is ethyl acetate; the above base membrane is taken out from the polyamide-imide organic solution, placed in an 80°C forced air oven and kept for 8 minutes, and a polysulfone composite nanofiltration membrane is obtained after drying.

[0091] At 25℃±2℃ and 0.31MPa pressure, the separation performance of the composite nanofiltration membrane was tested with 250ppm magnesium sulfate solution as the test water sample. The results are as follows: the desalination rate of the composite nanofiltration membrane is 93.1%, and the water flux is 40.4L / m 2 h.

[0092] In order to evaluate the anti-pollution ability of the composite nanofiltration membrane, industrial wastewater (organic wastewater, COD (chemical oxygen demand) greater than 600ppm, sulfate greater than 600ppm, amine nitrogen greater than 45ppm) was taken as the water sample at a pressure of 0.31MPa, and the composite nanofiltration membrane was run for 1h, and then the composite nanofiltration membrane was rinsed with pure water for 2 minutes; then at a pressure of 0.31MPa, 250ppm magnesium sulfate solution was used as the test water sample, and the separation performance of the composite nanofiltration membrane was retested. The results are as follows: the desalination rate of the composite nanofiltration membrane is 92.7%, and the water flux is 34.2L / m 2 h.

[0093] Embodiment 23

[0094] A polysulfone hollow fiber ultrafiltration membrane is used as a base membrane. The base membrane is first soaked in pure water, then taken out and washed with pure water, and then the washed base membrane is placed in the hyperbranched polyethyleneimine aqueous phase described in Example 11 and kept for 2 minutes; then the base membrane is taken out from the hyperbranched polyethyleneimine aqueous phase, hung vertically for 10 minutes, and the base membrane is drained; then the base membrane adsorbed with the aqueous phase is immersed in a polyamide-imide organic solution with a mass fraction of 0.40% and kept for 2 minutes, wherein the organic solvent is amyl acetate; the above base membrane is taken out from the polyamide-imide organic solution, placed in an 80°C forced air oven and kept for 8 minutes, and a polysulfone composite nanofiltration membrane is obtained after drying.

[0095] At 25℃±2℃ and 0.31MPa pressure, the separation performance of the composite nanofiltration membrane was tested with 250ppm magnesium sulfate solution as the test water sample. The results are as follows: the desalination rate of the composite nanofiltration membrane is 91.5%, and the water flux is 37.5L / m 2 h.

[0096] In order to evaluate the anti-pollution ability of the composite nanofiltration membrane, industrial wastewater (organic wastewater, COD (chemical oxygen demand) greater than 600ppm, sulfate greater than 600ppm, amine nitrogen greater than 45ppm) was taken as the water sample at a pressure of 0.31MPa, and the composite nanofiltration membrane was run for 1h, and then the composite nanofiltration membrane was rinsed with pure water for 2 minutes; then at a pressure of 0.31MPa, 250ppm magnesium sulfate solution was used as the test water sample, and the separation performance of the composite nanofiltration membrane was retested. The results are as follows: the desalination rate of the composite nanofiltration membrane is 91.2%, and the water flux is 33.4L / m 2 h.

[0097] Embodiment 24

[0098] A polysulfone hollow fiber ultrafiltration membrane is used as a base membrane. The base membrane is first soaked in pure water, then taken out and washed with pure water, and then the washed base membrane is placed in the hyperbranched polyethyleneimine aqueous phase described in Example 12 and kept for 2 minutes; then the base membrane is taken out from the hyperbranched polyethyleneimine aqueous phase, hung vertically for 10 minutes, and the base membrane is drained; then the base membrane adsorbed with the aqueous phase is immersed in a polyamide-imide organic solution with a mass fraction of 0.20% and kept for 2 minutes, wherein the organic solvent is cyclohexane; the above base membrane is taken out from the polyamide-imide organic solution, placed in an 80°C forced air oven and kept for 8 minutes, and a polysulfone composite nanofiltration membrane is obtained after drying.

[0099] At 25℃±2℃ and 0.31MPa pressure, the separation performance of the composite nanofiltration membrane was tested with 250ppm magnesium sulfate solution as the test water sample. The results are as follows: the desalination rate of the composite nanofiltration membrane is 90.6%, and the water flux is 38.2L / m 2 h.

[0100] In order to evaluate the anti-pollution ability of the composite nanofiltration membrane, industrial wastewater (organic wastewater, COD (chemical oxygen demand) greater than 600ppm, sulfate greater than 600ppm, amine nitrogen greater than 45ppm) was taken as the water sample at a pressure of 0.31MPa, and the composite nanofiltration membrane was run for 1h, and then the composite nanofiltration membrane was rinsed with pure water for 2 minutes; then at a pressure of 0.31MPa, 250ppm magnesium sulfate solution was used as the test water sample, and the separation performance of the composite nanofiltration membrane was retested. The results are as follows: the desalination rate of the composite nanofiltration membrane is 90.1%, and the water flux is 34.5L / m 2 h.

[0101] Among them, Example 1 is a specific implementation method for preparing hyperbranched polyethyleneimine; Examples 2-12 are specific implementation methods for preparing hyperbranched polyethyleneimine aqueous phase; Example 13 is a specific implementation method for preparing a composite nanofiltration membrane through the hyperbranched polyethyleneimine aqueous phase of Example 2; Examples 14-24 are the preparation and test results of composite nanofiltration membranes, as shown in Tables 1 and 2.

[0102] Table 1

[0103]

[0104] Table 2

[0105]

[0106] The above descriptions are only some specific embodiments of the present invention. The protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. Hyperbranched polyethyleneimine, characterized in that The preparation method of hyperbranched polyethyleneimine comprises the following steps: dissolving polyethyleneimine in an organic solvent to prepare an organic solution, wherein the mass fraction of polyethyleneimine in the organic solution is 0.01%-5.00%; adding alkali to the organic solution for reaction, wherein the alkali is a strong alkali, the alkali addition reaction time is 1-20h, and the temperature is 0-100°C; then adding glycidol with a mass of 50-1000 times that of polyethyleneimine to continue the reaction, and the reaction temperature is 80-200°C; after the reaction is continued, terminating with a terminator, filtering to obtain the hyperbranched polyethyleneimine; the terminator is one or more of methanol, ethanol and petroleum ether.

2. The hyperbranched polyethyleneimine according to claim 1, characterized in that The alkali is one or both of potassium hydroxide and sodium hydroxide.

3. The hyperbranched polyethyleneimine according to claim 1, characterized in that The organic solvent is one or more of amyl acetate, ethyl acetate and cyclohexane.

4. Hyperbranched polyethyleneimine aqueous phase, characterized in that The hyperbranched polyethyleneimine according to any one of claims 1 to 3 is dissolved in water to obtain a hyperbranched polyethyleneimine aqueous phase with a mass fraction of 0.20% to 2.0%.

5. A method for preparing a composite nanofiltration membrane, characterized in that: The following steps are involved: Step 1, soaking the base film in the hyperbranched polyethyleneimine aqueous phase as claimed in claim 4 once to obtain a base film with the hyperbranched polyethyleneimine aqueous phase attached to the surface; the base film material is one or more of polysulfone, polyethersulfone, polyacrylonitrile, polyimide, polyvinyl chloride, chlorinated polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyester fiber, polyvinyl alcohol fiber, polyetherimide, sulfonated polyetheretherketone, and cellulose acetate; Step 2: soak the base membrane with the hyperbranched polyethyleneimine aqueous phase attached to the surface in step 1 in a polyamideimide organic solution for a second time to obtain a composite nanofiltration membrane; the mass fraction of polyamideimide in the polyamideimide organic solution is 0.10%-1.0%.

6. The method for preparing a composite nanofiltration membrane according to claim 5, characterized in that: The solvent of the organic solution in step 2 is one or more of amyl acetate, ethyl acetate and cyclohexane.

7. A composite nanofiltration membrane, characterized in that: The method is described in any one of claims 5 to 6.

Citation Information

Patent Citations

  • Hyperbranched polymer-modified polymer film, and production method and application thereof

    CN107824057A

  • Preparation method of superhydrophilic anti-pollution PVDF (polyvinylidene fluoride) separation membrane

    CN108404684A

  • Preparation and application of sulfur-containing hyperbranched polyglycerol copolymer

    CN109021229A

  • Polycaffeic acid / hyperbranched polymer composite nanofiltration membrane, and preparation method and application thereof

    CN110721601A

  • Sulfonated polyethyleneimine and nanofiltration membrane, and preparation methods thereof

    CN111187413A